Hot and cold hands on the PGA Tour: Do they exist? - Elmore, R.; Urbaczewski, A. (Journal of Sports Analytics, 2018)
In this paper, we examine the "hot hand" (and "cold hand") phenomenon as it relates to the PGA Tour using data from the 2013-4 PGA Tour season. For this study, we define "hot hand" in golf as having a greater probability of recording a birdie or better on a hole immediately following a birdie or better. Similarly, a "cold hand" is thought of as having a greater probability of recording a bogey or worse following a bogey or worse. The basis of our hot/cold hand model is centered around each hole`s relative difficulty on a particular day, the actual par rating of the hole, and a random player effect. Our results seem to agree with most of the related work on hot hand effects in basketball, golf, and other sports; namely, that there is simply not enough evidence to suggest that the hot hand phenomenon exists. On the other hand, the presence of a cold hand effect is highly significant, particularly on par 4 holes. Finally, we present the development and results of a large-scale power analysis simulation study in support of our proposed methodology.